Development Of Nature Tourism And Cultural Tourism By The Baubau City Tourism Office, Southeast Sulawesi Province - Muh, Maulid Agus; Dyah Poespita Ernawati; Layla Kurniawati (Jurnal Scientia, 2024)
Competition in tourism development between regions shows that tourism has the potential to have a positive impact. The Indonesian tourism sector experienced a decline in the number of tourist visits due to the Covid-19 pandemic. However, currently tourism is starting to recover and revive. It is hoped that tourism development will make Baubau City tourism more advanced and Baubau become a tourist destination city in Indonesia. Tourist attractions that can be developed are the natural tourist attraction Batu Sori and the cultural tourist attraction Buton Palace Fort. This research aims to analyze and describe the development of natural tourism in Batu Sori and cultural tourism in the Buton Palace Fort, then describe the supporting and inhibiting factors for development activities, as well as determine the efforts made by the Tourism Office in overcoming obstacles related to the development of tourist attractions. The research was carried out using research methods qualitative descriptive. The techniques used to collect data are observation, interviews and documentation. Analyzing data using data reduction techniques, data display and drawing conclusions and verification. The results of the research explain that the development of the Batu Sori natural tourist attraction and the Buton Palace Fort cultural tourist attraction is not yet in accordance with the goals and objectives, due to budget limitations, the Sapta Pesona value is not fulfilled, the two tourist attractions are not connected to public transportation, the active role of the community or tourists is still lacking in maintaining and maintaining the environment of tourist attractions, the number and competence of tourism human resources is inadequate, and there are no regional regulations related to the Buabau City Regional Tourism Development Master Plan. Efforts made by the Tourism Office include building infrastructure facilities, providing tourism training activities, coordinating with other regional apparatus, utilizing regional financial resources and drafting regional regulations for special areas.